Analisis Strategi Preventif Polis Lapse Akibat Keterlambatan dalam Pembayaran Premi Lanjutan (Studi Kasus pada PT Asuransi Jiwa Syariah Bumiputera KPS Medan) - Rahma, Meutia Maulida; Batubara, Maryam; Tambunan, Khairina (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Lapse policy is the termination of insurance suspension due to non-payment of premiums. A customer whose policy is in a state of lapse, if he experiences an accident covered by the policy, his claim will be rejected. PT. Bumiputera KPS Medan Sharia Life Insurance has increased every year but the number of policies declared lapsed has also increased. For this reason, a preventive strategy is needed to reduce the occurrence of policy lapses due to delays in premium payments. This study aims to determine the impact caused by the policy lapse, as well as to determine the prevention strategy undertaken by PT. Bumiputera KPS Medan Sharia Life Insurance in overcoming and preventing policy lapse. This research is a type of descriptive research with a qualitative approach. Data collection techniques were carried out by semi-structured interviews, observation and documentation. The data analysis technique used SWOT analysis, data reduction, data presentation, and drawing conclusions. From the results of the Cartesian diagram, it shows that the company is in quadrant I, namely an aggressive strategy, where this quadrant is a very profitable situation. The strategy that must be applied in this condition is to support an aggressive growth policy (Growth Oriented Strategy). This strategy indicates the company’s condition is strong and able to continue to grow by taking the opportunities or opportunities that exist.